The crab Relish plays an important role in white spot syndrome virus and Vibrio alginolyticus infection. Issue 87 (April 2019) - Zhu, Fei; Sun, Baozhen; Wang, Ziyan
Abstract: Relish is a transcription factor and forms an important part of the immune deficiency signaling pathway. In the current study, a Relish homolog was cloned from the hemolymph of Scylla paramamosain using RT-PCR and RACE. The full length cDNA of Relish consists of 4263 base pairs (bp), including a 3552 bp open reading frame encoding a 1184 amino acid protein. The data showed that Relish was highly expressed in the gonad and digestive organs of S. paramamosain . Furthermore, the expression of Relish was up-regulated by infection with white spot syndrome virus (WSSV) or Vibrio alginolyticus . When Relish was knocked down, immune genes such as Janus Kinase, signal transducer and activator of transcription, crustin antimicrobial peptide, prophenoloxidase, C-type-lectin and myosin-II-essential-light-chain-like-protein were significantly down-regulated ( P < 0.01), and Toll-like receptor was significantly up-regulated ( P < 0.01) in hemocytes. The mortality of WSSV-infected or V. alginolyticus -infected crabs was enhanced following Relish knockdown. Thus, Relish is very important in the progression of WSSV and V. alginolyticus infection. It was found that Relish knockdown caused the highest level of apoptosis in the disease-free group, and higher levels of apoptosis in the WSSV group and V. alginolyticus group compared with that in the control group. Knockdown of Relish influenced the activity of phenoloxidase (PO) and superoxide dismutase (SOD), and total hemocyte count (THC) following WSSV or V. alginolyticus infection, indicating that Relish plays a regulatory role in the immune response to WSSV or V. alginolyticus infection in crabs. Thus, we conclude that Relish may anticipate host defense mechanisms against pathogen infection by affecting apoptosis, THC, PO activity and SOD activity. Highlights: Relish was up-regulated by infection with WSSV or Vibrio alginolyticus. The mortality of WSSV-infected or V. alginolyticus -infected crabs was enhanced following Relish knockdown. Relish may regulate apoptosis, THC, PO activity and SOD activity.